2009
DOI: 10.1016/j.eujps.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of drugs in regional anesthesia: A review

Abstract: Local anesthetics and opioids are the most commonly used drugs in regional anesthesia. Several other drugs are used as adjuvants in addition to local anesthetics. We will review the drugs currently used in regional anesthesia. In April 2009 we searched the PubMed database and found 143 articles related to the clinical use of drugs in regional anesthesia; we divided them into 3 major chapters: local anesthetics, opioids and adjuvants. Among local anesthetics, ropivacaine and levobupivacaine can be considered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 160 publications
(153 reference statements)
0
2
0
1
Order By: Relevance
“…5 Beberapa obat anestesi lokal, yaitu ropivakain dan levobupivakain dapat menjadi obat pilihan pada blokade neuroaksial karena memiliki toksisitas yang rendah meskipun diberikan dalam jumlah yang banyak. 6 Bupivakain merupakan obat anestesi lokal yang sangat kardiotoksik, namun masih menjadi obat anestesi lokal yang paling banyak digunakan oleh dokter anestesi 7 termasuk di Jawa Barat. Hal ini dikarenakan harganya yang lebih murah dan mudah didapat dibanding dengan ropivakain maupun levobupivakain.…”
Section: Pembahasanunclassified
“…5 Beberapa obat anestesi lokal, yaitu ropivakain dan levobupivakain dapat menjadi obat pilihan pada blokade neuroaksial karena memiliki toksisitas yang rendah meskipun diberikan dalam jumlah yang banyak. 6 Bupivakain merupakan obat anestesi lokal yang sangat kardiotoksik, namun masih menjadi obat anestesi lokal yang paling banyak digunakan oleh dokter anestesi 7 termasuk di Jawa Barat. Hal ini dikarenakan harganya yang lebih murah dan mudah didapat dibanding dengan ropivakain maupun levobupivakain.…”
Section: Pembahasanunclassified
“…Improvement in patient outcomes has been achieved with the use of regional anesthesia techniques, both neuraxial and peripheral nerve blocks. Mortality, major morbidity, and patient‐oriented outcomes have been demonstrated to improve with neuraxial techniques, particularly with epidural anesthesia and continued epidural analgesia (Grossi et al, 2010; Allegri et al, 2009; Capdevila et al, 1999; Liu et al, 1995) Meta‐analyses have also reported improved surgical outcomes (without a reduction in mortality or morbidity) associated with single‐injection and continuous plexus and peripheral analgesic techniques (Capdevila et al, 1999; Maier et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Regional anesthesia (RA) encompasses both central neuraxial blockade and peripheral nerve block techniques that can use effective and safe drugs such as local anesthetics, opioids, and other adjuvants (Ilfeld et al, 2008; Allegri et al, 2009). These techniques can be used as the sole anesthetic technique or in conjunction with general anesthesia or sedation (Ballantyne et al, 2005), and in recent years the continuous (epidural and peripheral) blocks have been used for postoperative pain (POP) management.…”
Section: Introductionmentioning
confidence: 99%